Comparação do tempo de recuperação pós-anestésica em pacientes sedados para colonoscopia usando midazolam ou fentanil associados a propofol - Gisela Magnus (2020)
Objective: Comparison of post-anesthesia recovery time in sedated patients for colonoscopy using two drug combinations: midazolam and propofol or fentanyl and propofol. Method: Fifty patients ASA I and II, from 18 to 65 years of age, candidates for elective colonoscopy under sedation administered by an anesthesiologist, were randomized in two groups: Group A (midazolam and propofol) and Group B (fentanyl and propofol). Each patient was evaluated as for the length of the exam (Exam length), length of stay in the post-anesthesia care unit 1 and 2 (LSPACU1 and LSPACU2) and hospital discharge. Episodes of awakening, and of movement, drop in SpO2 < 90%, need for mechanical ventilation, propofol consumption, heart rate (HR) and mean blood pressure (MBP) were also evaluated. Results: Patients of group B had a recovery time in LSPACU1 statistically shorter than that for those in group A. In both groups, LSPACU1 was considered inversely proportional to LSPACU2. Hospital discharge time was similar between groups. Patients of group B had a significant decrease in MBP during and at the end of the exam, when compared to the initial measurement and that during sedation. Nevertheless, this variation was lower than 20%. No adverse event was observed. All patients were discharged on the same day, with no unexpected hospitalization. Conclusions: The combined use of fentanyl and propofol for colonoscopy sedation was shown to be safe and had a post-anesthesia recovery time in LSPACU1 shorter than that with the combination of midazolam and propofol. The reduction of this time may increase safety and reduce procedure costs.